IMPLEMENTASI ALGORITMA ADVANCED ENCRYPTION STANDARD (AES) E-ASPIRASI MAHASISWA PADA FAKULTAS SAINS DAN TEKNOLOGI BERBASIS WEB - Mayasari Mayasari; Suendri Suendri; M Fakhriza (JISTech (Journal of Islamic Science and Technology), 2022)
Student aspirations are various demands that are packaged in students' creative ideas that propose a process of changing something. There is no aspiration complaint service system at the Fakultas Sains dan Teknologi, Universitas Islam Negeri Sumatera Utara. So that students do not have a place to express their aspirations. Along with the development of technology, a web-based student complaint application was made which is equipped with the AES (Advanced Encryption Standard) algorithm which is able to secure student aspiration messages so that the aspiration messages conveyed by students cannot be read by other students, so that student aspiration messages are more confidential. The design and manufacture of this web-based public complaint application uses the waterfall model. The waterfall model begins with the analysis stage, namely by analyzing and collecting data through interviews with students and the Administration of the Faculty of Science and Technology, the system design stage, namely by designing the system interface, the system coding stage, and this stage ends with the system testing stage. Carried out to determine the feasibility of the system.